Demographic, socioeconomic and dietary factors are associated with double burden of malnutrition among indigenous communities in Sarawak - Yolanda, Salleh; Cheah, Whye Lian; Law, Leh Shii; Jeffery, Stephen; Teoh, Wan Jool (Nutrition Society of Malaysia, 2024)
Introduction: Double burden of malnutrition (DBM), encompassing both overnutrition and undernutrition, is a growing global public health issue. Indigenous people are one of the marginalised populations experiencing DBM at varying severity. This study aimed to identify factors contributing to DBM in indigenous households in Sarawak. Methods: This cross-sectional study utilised multistage random sampling to include 286 indigenous households from six administrative divisions in Sarawak. Mothers aged 20–49 years who had at least one child aged 2–12 years were recruited. Trained interviewers obtained information on demographic and socioeconomic characteristics, food security, and dietary intake via a two-day, 24-hour dietary recall. Height and weight measurements followed World Health Organization protocols. DBM household was identified as having an overnourished (overweight/ obese) mother with an undernourished (underweight/stunting/wasting) child within the same household. Simple and multiple binary logistic regression analyses were performed. Results: Prevalence of DBM among the indigenous communities in Sarawak was 25.2%. Households with an overweight/obese mother and a stunted child was 12.9%, wasted child (11.9%), and underweight child (9.4%). Households with younger mothers, a household size of >4 persons, and higher income per capita (relative to sample population) were significantly more likely to have DBM. Conversely, households with higher monthly non-food expenditure and greater fish and seafood intake scores in children were significantly less likely to have DBM. Conclusion: DBM is prevalent among Sarawak’s indigenous communities, affecting 25.2% of households. Further research and targeted interventions are needed to address socioeconomic and dietary factors in these populations.